Serotonin enhances neurogenesis biomarkers, hippocampal volumes, and cognitive functions in Alzheimer’s disease - Ali Azargoonjahromi; For the Alzheimer’s Disease Neuroimaging Initiative (Molecular Brain)
Abstract Research on serotonin reveals a lack of consensus regarding its role in brain volume, especially concerning biomarkers linked to neurogenesis and neuroplasticity, such as ciliary neurotrophic factor (CNTF), fibroblast growth factor 4 (FGF-4), bone morphogenetic protein 6 (BMP-6), and matrix metalloproteinase-1 (MMP-1) in Alzheimer’s disease (AD). This study aimed to investigate the influence of serotonin on brain structure and hippocampal volumes in relation to cognitive functions in AD, as well as its link with biomarkers like CNTF, FGF-4, BMP-6, and MMP-1. Data from 133 ADNI participants with AD included cognitive assessments (CDR-SB), serotonin measurements (Biocrates AbsoluteIDQ p180 kit, UPLC-MS/MS), and neurotrophic factors quantified via multiplex proteomics. Gray matter volume changes were analyzed using Voxel-Based Morphometry (VBM) with MRI. Statistical analyses employed Pearson correlation, bootstrap methods, and FDR-adjusted p-values (< 0.05 or < 0.01) via the Benjamini–Hochberg procedure, alongside nonparametric methods. The analysis found a positive correlation between serotonin levels and total brain (r = 0.229, p = 0.023) and hippocampal volumes (right: r = 0.186, p = 0.032; left: r = 0.210, p = 0.023), even after FDR adjustment. Higher serotonin levels were linked to better cognitive function (negative correlation with CDR-SB, r = −0.230, p = 0.024). Notably, serotonin levels were positively correlated with BMP-6 (r = 0.173, p = 0.047), CNTF (r = 0.216, p = 0.013), FGF-4 (r = 0.176, p = 0.043), and MMP-1 (r = 0.202, p = 0.019), suggesting a link between serotonin and neurogenesis and neuroplasticity. However, after adjusting for multiple comparisons and controlling for confounding factors such as age, gender, education, and APOE genotypes (APOE3 and APOE4), none of the correlations of biomarkers remained statistically significant. In conclusion, increased serotonin levels are associated with improved cognitive function and increased brain volume. However, associations with CNTF, FGF-4, BMP-6, and MMP-1 were not statistically significant after adjustments, highlighting the complexity of serotonin’s role in AD and the need for further research. Graphical Abstract